Ubiquitous Gammaproteobacteria dominate dark carbon fixation in coastal sediments - Dyksma, Stefan; Bischof, Kerstin; Fuchs, Bernhard M; Hoffmann, Katy; Meier, Dimitri; Meyerdierks, Anke; Pjevac, Petra; Probandt, David; Richter, Michael; Stepanauskas, Ramunas; Mußmann, Marc (The ISME Journal, 2016)
Marine sediments are the largest carbon sink on earth. Nearly half of dark carbon fixation in the oceans occurs in coastal sediments, but the microorganisms responsible are largely unknown. By integrating the 16S rRNA approach, single-cell genomics, metagenomics and transcriptomics with 14 C-carbon assimilation experiments, we show that uncultured Gammaproteobacteria account for 70–86% of dark carbon fixation in coastal sediments. First, we surveyed the bacterial 16S rRNA gene diversity of 13 tidal and sublittoral sediments across Europe and Australia to identify ubiquitous core groups of Gammaproteobacteria mainly affiliating with sulfur-oxidizing bacteria. These also accounted for a substantial fraction of the microbial community in anoxic, 490-cm-deep subsurface sediments. We then quantified dark carbon fixation by scintillography of specific microbial populations extracted and flow-sorted from sediments that were short-term incubated with 14 C-bicarbonate. We identified three distinct gammaproteobacterial clades covering diversity ranges on family to order level (the Acidiferrobacter , JTB255 and SSr clades) that made up >50% of dark carbon fixation in a tidal sediment. Consistent with these activity measurements, environmental transcripts of sulfur oxidation and carbon fixation genes mainly affiliated with those of sulfur-oxidizing Gammaproteobacteria . The co-localization of key genes of sulfur and hydrogen oxidation pathways and their expression in genomes of uncultured Gammaproteobacteria illustrates an unknown metabolic plasticity for sulfur oxidizers in marine sediments. Given their global distribution and high abundance, we propose that a stable assemblage of metabolically flexible Gammaproteobacteria drives important parts of marine carbon and sulfur cycles.